Batch‐to‐batch pharmacokinetic variability confounds current bioequivalence regulations: A dry powder inhaler randomized clinical trial. Issue 3 (28th April 2016) - Burmeister Getz, E; Carroll, KJ; Jones, B; Benet, LZ
Abstract : Current pharmacokinetic (PK) bioequivalence guidelines do not account for batch‐to‐batch variability in study design or analysis. Here we evaluate the magnitude of batch‐to‐batch PK variability for Advair Diskus 100/50. Single doses of fluticasone propionate and salmeterol combinations were administered by oral inhalation to healthy subjects in a randomized clinical crossover study comparing three different batches purchased from the market, with one batch replicated across two treatment periods. All pairwise comparisons between different batches failed the PK bioequivalence statistical test, demonstrating substantial PK differences between batches that were large enough to demonstrate bio‐ in equivalence in some cases. In contrast, between‐replicate PK bioequivalence was demonstrated for the replicated batch. Between‐batch variance was ∼40–70% of the estimated residual error. This large additional source of variability necessitates re‐evaluation of bioequivalence assessment criteria to yield a result that is both generalizable and consistent with the principles of type I and type II error rate control.